THE LANGUAGE STYLE OF Dr. ZAKIR NAIK’S SPEECH (A PRAGMASTYLISTIC STUDY OF SPEECH ACTS) - Lailatul Fitriyah (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Universitas Hasyim Asy'ari (Unhasy), 2021)
Abstract: People are created to be a social human being, and communication becomes a very crucial thing for humans’ lives to continously share their ideas and speaks up their mind to each other. The act of communication that becomes one of the aspects of communication in pragmastylistic field is defined for speech act. This study explores the style performed by Dr Zakir Naik in his stage of speech and his intended communicative effect to his audience. By doing this research, the writer intends to find out 1) what style of speech act is used in Dr. Zakir Naik’s speeches and and 2) how the context influences the choice of speech acts in Dr. Zakir Naik’s speeches. The method used in this study is qualitative research method. The theory used in this study is Searle’s speech acts theory (1979). The researcher observes a video of Zakir Naik’s speech from youtube. This research reveals that the style of speech which Dr Zakir Naik dominantly used while he explains, informs and emphasizes the content of his speech to the audiences is illucotionary acts. There are several kinds of illucotionary acts such as: Assertive, Directive, Commissive, Expressive, and Declarative. However, assertive and directive are chosen as his favorite rethoric in his speeches. Further research is expected to invistigate the critical discourse analysis on Dr. Zakir Naik’s speeches in order to determine the social politic value and to analyse the specific structure of his speech more deeply. Keywords: Style of Speech, Speech acts, Illucotionary Acts, Pragmastylistic, Linguistic. Abstrak: Manusia diciptakan untuk menjadi manusia sosial, dan komunikasi menjadi hal yang sangat penting bagi kehidupan manusia untuk senantiasa berbagi ide dan mengutarakan pendapatnya satu sama lain. Tindak komunikasi yang menjadi salah satu aspek komunikasi dalam bidang pragmastilistik diartikan sebagai tindak tutur. Studi ini mengeksplorasi gaya yang dibawakan oleh Dr Zakir Naik dalam tahap pidatonya dan efek komunikatif yang diinginkannya kepada para pendengarnya. Dengan melakukan penelitian ini, penulis bermaksud untuk mengetahui 1) gaya tindak tutur yang digunakan dalam ceramah Dr. Zakir Naik dan 2) bagaimana konteks mempengaruhi pilihan tindak tutur dalam ceramah Dr. Zakir Naik. Metode yang digunakan dalam penelitian ini adalah metode penelitian kualitatif. Teori yang digunakan dalam penelitian ini adalah teori tindak tutur Searle (1979). Peneliti mengamati video pidato Zakir Naik dari youtube. Penelitian ini mengungkapkan bahwa gaya bicara dominan yang digunakan oleh Dr. Zakir Naik saat menjelaskan, menginformasikan dan menekankan isi pidatonya kepada khalayak adalah tindak ilokusi. Ada beberapa macam tindak ilokusi seperti: Assertive, Directive, Commissive, Expressive, dan Declarative. Namun, assertive dan directive dipilih sebagai rethoric favorit dalam pidatonya. Penelitian lebih lanjut diharapkan dapat menginvestigasi analisis wacana kritis pidato Dr.Zakir Naik untuk mengetahui nilai sosial politik dan menganalisis struktur spesifik pidatonya lebih dalam. Kata Kunci : Gaya Pidato, Tindak Tutur, Tindak Ilokusi, Pragmastilistik, Linguistik